2023
DOI: 10.3390/microorganisms11020414
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Fermentation of Edible Mushrooms: Effects on Faecal Microbiota Characteristics of Autistic and Neurotypical Children

Abstract: Children with autism spectrum disorder (ASD) often suffer gastrointestinal disturbances consistent with gut microbiota (GM) alterations. Treatment with pro/prebiotics may potentially alleviate gut symptoms, but the evidence for prebiotics is scarce. This study aims to evaluate the effects of edible mushrooms (Pleurotus, Basidiomycota) and prebiotic compounds on GM composition and metabolite production in vitro, using faecal samples from autistic and non-autistic children. Specific microbial populations were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 74 publications
0
0
0
Order By: Relevance
“…and Bifidobacterium spp. compared to ASD children [15]. In the same pattern, the study of Ding et al [30] demonstrated that children with ASD showed an altered GM structure compared with children in the healthy control group.…”
Section: Dysbiosis In Autism Spectrum Disordermentioning
confidence: 79%
See 3 more Smart Citations
“…and Bifidobacterium spp. compared to ASD children [15]. In the same pattern, the study of Ding et al [30] demonstrated that children with ASD showed an altered GM structure compared with children in the healthy control group.…”
Section: Dysbiosis In Autism Spectrum Disordermentioning
confidence: 79%
“…This bidirectional communication within the gut-brain axis elucidates how messages from the GM influence brain function and how signals from the brain impact gastrointestinal physiology and gut microbial activity [17]. These bidirectional communications involve the central nervous system (CNS), intrinsic branches of the enteric nervous system (ENS), extrinsic parasympathetic and sympathetic branches of the autonomic nervous system (ANS), the hypothalamic-pituitary-adrenal axis (HPA), neuroimmune pathways (neurotransmitters, hormones, and neuropeptides), and the gut microenvironment [15,18]. The HPA axis, a component of the limbic system, is considered the central stress efferent axis that coordinates the organism's adaptive responses to all stressors.…”
Section: The Gut-brain Axismentioning
confidence: 99%
See 2 more Smart Citations